On the complexity of the ideal of absolute null sets - Zakrzewski, P. (Український математичний журнал, 2012)
Answering a question posed by Banakh and Lyaskovska, we prove that, for an arbitrary countable infinite amenable group G, the ideal of sets having μ-measure zero for every Banach measure μ on G is an Fσδ subset of {0; 1}G.